ACTUALIZATION OF THE PROBLEM OF FORMATION OF SPIRITUAL AND MORAL QUALITIES OF SENIOR ADOLESCENTS BY MEANS OF MUSIC ART - Бузовська, Л.М.; Брежнєва, С.Б. (SWorldJournal, 2022)
The problem of the spiritual and moral and the aesthetic education of teenagers has been highlighted in the publication and the reference-point of the formation of the spiritual and moral qualities in them by means of art have been denoted. The authors re